The Concept of Islamic Parenting in the Era of Islamic Moderation: An Analysis of Hurlock's Parenting Theory - Vivi Yulia Nora (Islam Transformatif : Journal of Islamic Studies, 2021)
AbstractThis article describes the parenting proposed by Hurlock and its relevance to parenting in Islam in the face of Islamic moderation demands. This research is comparative research with data analysis techniques using content analysis and descriptive analysis. This research concludes that there are two Hurlock’s parenting patterns related to Islamic parenting, namely authoritarian and democratic parenting. In Islamic Parenting, parents parenting is not authoritarian and not too permissive towards children; this is in line with the concept of Wasatiyyah in Islam, which means in the middle. This parenting is one of the examples of Noah AS., Ibrahim AS., and Luqman as told int the Qur’an, and the example og prophet Muhammad SAW., in the Sunnah. To face the moderation of Islam, parents can apply these two parenting styles to their children. Through moderate but still Islamic parenting, it is hoped that it can make a generation that can become part of the "ummatan wasaṭan", namely a generation that has good, fair, and not extreme characters, and is independent, not taking sides except for what is right according to the teachings of the Shari'a.Keyword: Parenting, Hurlock, Islamic Parenting, Moderation of IslamAbstrakArtikel ini memaparkan tentang pola asuh yang dikemukakan oleh Hurlock dan relevansinya dengan parenting dalam Islam dalam menghadapi tuntutan moderasi Islam. Penelitian ini adalah penelitian komparatif dengan teknik analisis data menggunakan analisis konten dan analisis deskriptif. Adapun kesimpulan dari peneltian ini adalah bahwa terdapat dua pola asuh Hurlock yang memiliki keterkaitan dengan parenting Islami, yaitu pola asuh otoriter dan demokratis. Dalam Pola Asuh Islami orang tua dalam pengasuhan Anak tidak otoriter dan tidak terlalu permisif terhadap anak, hal imi senada dengan konsep Wasatiyyah dalam Islam yang artinya ditengah Pola asuh tersebut merupakan salah satu keteladanan Nabi Nuh As., Nabi Ibrahim AS., dan Luqman yang diceritakan dalam al-Qur’an, serta keteladanan Nabi Muhammad dalam Sunnah. Untuk menghadapi moderasi Islam dua pola asuh tersebut dapat diterapkan oleh orang tua terhadap anaknya. Melalui pola asuh moderat namun tetap islami diharapkan dapat menjadikan generasi yang mampu menjadi bagian dari “ummatan wasaṭan”, yaitu generasi yang memiliki karakter baik, adil, dan tidak ekstrem, serta bersifat independen, tidak berpihak kecuali kepada hal yang benar menurut ajaran syariat. Kata Kunci: Pola Asuh, Hurlock, Parenting Islami, Moderasi Islam